Bending behavior of steel-UHPC composite bridge deck based on epoxy adhesive - Li, Baojun; Jiang, Jinlong; Deng, Zhiheng; Zhou, Heying; Wang, Haicui; Jiang, Haoting; Cao, Yidong (Frontiers in Materials, 2022)
Using ultra-high performance concrete (UHPC) as the pavement layer on the orthotropic steel deck (OSD) can greatly enhance the rigidity to solve the fatigue cracking of the steel deck and the resulting damage to the pavement layer. However, the thin UHPC layer limits the extensive use of the short stud connector. In this study, three types of interfaces were designed by introducing different additives into the epoxy matrix, and the shear properties of each interface and short stud connector were compared. Then, the influence of short stud connectors and optimized interface on the composite bridge deck’s bending property was analyzed through the composite bridge deck’s bending test. Moreover, the mechanical behavior of the interface in the composite bridge deck is discussed based on the finite element model. The results show that the ultimate load of the composite bridge deck with the optimized interface is reduced by 21.5% compared with that of the composite bridge deck with the short stud connector. However, the composite bridge deck with the optimized interface has higher bending stiffness before failure and is less affected by cyclic loading. Moreover, the composite bridge deck with the optimized interface is unsuitable for cyclic loading conditions when the defect area reaches 30%. Finally, the numerical simulation of the composite bridge deck with the optimized interface is successfully realized based on the cohesive zone model, and the applicability of the interface in the composite bridge deck is verified.